Experimental Study on Mechanical Properties of Structured Clay under Different Unloading Rates and Unloading Stress Paths - Lu Li; Meng Zang; Rongtang Zhang; Haijun Lu (Buildings, 2023)
Consolidated undrained triaxial shear tests were performed on undisturbed saturated structured clay at three unloading rates (0.1, 0.25, and 2.5 kPa/min) using a GDS triaxial system to determine the effects of different unloading rates and unloading stress paths on the stress–strain relationship, pore pressure variation, and failure strength characteristics of Zhanjiang structured clay. Microstructural changes in the clay were observed during shear tests at different unloading rates. Furthermore, the obtained stress–strain relationship indicates strain-softening under different unloading stress paths. Under the same axial strain, a larger unloading rate caused a larger deviatoric stress. Under the same conditions, the higher the confining pressure, the greater the peak pore pressure, the smaller the unloading rate, the greater the pore pressure development, and the greater the variation in the pore pressure. Moreover, the undrained shear strength increased with an increase in the unloading rate from 0.1 to 2.5 kPa/min. The change in the unloading rate had a greater effect on the undrained strength under the passive tensile path than that under the passive compression path. The microstructure of the Zhanjiang structured clay changed after shear tests at different unloading rates, exhibiting various degrees of adjustment in the particle arrangement, contact relations, pore sizes, and shapes.